Thrombotic Thrombocytopenic Purpura due to Checkpoint Inhibitors - Youssef, Alexey; Kasso, Nawara; Torloni, Antonio Sergio; Stanek, Michael; Dragovich, Tomislav; Gimbel, Mark; Mahmoud, Fade (Case Reports in Hematology, 2018)
Ipilimumab is a monoclonal antibody that enhances the efficacy of the immune system by targeting a cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), which is a protein receptor that downregulates the immune system. Nivolumab is also a humanized monoclonal antibody that targets another protein receptor that prevents activated T cells from attacking the cancer; this receptor is called programmed cell death 1 (PD-1). The FDA approved ipilimumab combined with nivolumab as a frontline therapy for patients with metastatic melanoma or renal cell carcinoma and as a second-line therapy for patients with microsatellite instability-high (MSI-H) metastatic colon cancer. Immune-related adverse events such as autoimmune colitis, pneumonitis, hepatitis, nephritis, hypophysitis, and thyroiditis may occur during or weeks to months after therapy. We report a case of thrombotic thrombocytopenic purpura (TTP) in a patient with metastatic renal cell carcinoma following one cycle of ipilimumab and nivolumab. Only one case report of ipilimumab-induced TTP exists in the medical literature. With the wide use of immunotherapy to treat cancers, physicians need to be aware of this rare immune-related adverse event.